Konsep Diri Pengamen Angklung di Jalan Sudirman, Kecamatan Patrang, Kabupaten Jember - Yoga Parulian Panggabean; Mochammad Fiki Eko Syahputra Yudhoyono; Dhiyaul Haqqi Al-Mumtaza (Pusat Riset dan Inovasi Nasional, 2023)
Street buskers on Sudirman Street, Patrang District, Jember Regency are one of the buskers who use angklung musical instruments as their medium to earn income in their daily lives. This study aims to determine the individual lives of angklung buskers on Sudirman Street, Patrang, Jember by using qualitative methods and primary data sources obtained directly. Data collection techniques used through observation, interviews and documentation. The results of this study explain that there are factors driving individuals to choose to work as angklung buskers rather than choosing other jobs. The things that underlie individuals working as angklung buskers are supported by the low economic background of the individual and the individual's hobby of angklung music. The activities of this Jember angklung busker begin in the morning until the evening with an income of around Rp. 50,000 / day. In the phenomenon of angklung buskers in Jember, it can be seen that individuals have certain reasons for living their daily lives as angklung buskers. On the one hand, as the general public we cannot give bad assumptions to individuals who work as angklung buskers or other types of buskers without knowing the background of the individual concerned.